Transforming borders : Chicana/o popular culture and pedagogy - Elenes, C. Alejandra, 1958- (Lexington Books, 2011)
Transforming Borders: Chicana/o Popular Culture and Pedagogy situates Chicana feminists' re-imagining of La Llorona, the Virgin of Guadalupe, and Malintzin/Malinche as sources of border/transformative pedagogies. In doing so, C. Alejandra Elenes contributes to the scholarship on transformative pedagogies by adding the voices of Chicana feminist pedagogies, epistemologies, and ontologies. Linking the relationship between cultural practices, knowledge, and teaching in everyday life, Elenes develops h er conceptualization of border/transformative pedagogies.